Equity of transit connectivity in Tennessee cities - Sharma, Ishant; Mishra, Sabyasachee; Golias, Mihalis; Welch, Timothy F.; Cherry, Christopher R. (My University, 2020)
Federal and state agencies focus on providing captive users in mobility-vulnerable population groups with access to public transit resources. One challenge to the provision of equitable access is quantifying equity-oriented metrics for public transit service. This paper utilizes an approach that utilizes the available spatial demographic data and transit network characteristics to compute multimodal transit connectivity and equity. This method is exemplified by analyzing transit connectivity for three metropolitan cities in the state of Tennessee in the United States and overlapping that connectivity on demographic data. Results indicate that the distribution of transit services among vulnerable populations varies within and between cities. The case studies illustrate how this methodology can be used by public agencies to assess the performance of transit systems and to identify the distribution of these systems among various groups to improve the equity of transit connectivity.
Keywords: Public transit; Connectivity; Equity; Gini index; Open-source data